Forum «Olympic Sport : history and modern times» - Вадим Фельдман (National University of Physical Education and Sport of Ukraine, 2017)
The review article discusses a set of measures included in the program of the Forum «Olympic Sports: history and modern times» dedicated to the 25th anniversary of the Olympic Academy of Ukraine that was held in December 2016 at the National university of physical education and sport of Ukraine in Kiev. The article tells both about a festive ceremony dedicated to the Jubilee of the OAU and its ХVII-th reporting-election session, and about International Conference «Actual problems of modern Olympic education», all-Ukrainian seminar «Comprehensive school is a source of knowledge, human and Olympic values», the seminar «Current state and prospects of development of the theory and methodology of sports training» and 'round table conference' «From Rio de Janeiro- 2016 to Tokyo-2020: the effectiveness of training of top Ukrainian athletes» that were held on the same days at the NUPESU.